Efficacy and mechanism of Shuiluerxian Pills for diabetic nephropathy through a regulation of PI3K/AKT signaling pathway - Yan-ling Rao; Qin-guo Sun; Wei Huang (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To explore the therapeutic mechanism of Shuiluerxian Pills (SP) for diabetic kidney disease (DKD) with the aids of network pharmacological methods and in vivo experiments. Methods The active components and related targets of SP were screened by the TCM Systematic Pharmacological database and analysis platform (TCMSP). The above chemical constituents and target information were supplemented by literature searches to further correlating the target of DKD in the disease database. Protein-protein interaction (PPI) network was constructed with the String software. Enrichment analysis was performed with R language and complex network model established. The levels of tumor necrosis factor alpha (TNF-α), interleukin-6 (IL-6) and IL-1β in kidney were detected by enzyme-linked immunosorbent assay (ELISA) and the expressions of key proteins verified by Western blot. The pharmacodynamic mechanism of SP for DKD was preliminarily predicted. Results A total of 376 potential DKD therapeutic targets were identified. The "composition-disease-target" network diagram implied that kaverol and astragaloside IV were the major active components of SP formula to play the therapeutic role of DKD. Its common pathways were correlated with the pathways of phosphatidylinositol 3 kinase (PI3K)/protein kinase B (Akt) and advanced glycation end products (AGEs)-receptor for advanced glycation end products (RAGE). The experimental results indicated that SP could effectively reduce the level of inflammatory factors in diabetic rats, enhance the protein expressions of Nephrin and Podocin and lower the protein expressions of p-PI3K/PI3K and p-Akt/Akt. Conclusions SP may play a role in the treatment of DKD through regulating PI3K/Akt signaling pathway, suppressing inflammatory responses and renal tissue fibrosis. The treatment of DKD offers the characteristics of multi-component, multi-target and multi-pathway.